2019
DOI: 10.1142/s0129065718500119
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Seizure Detection Using Deep Convolutional Neural Networks

Abstract: Identifying a core set of features is one of the most important steps in the development of an automated seizure detector. In most of the published studies describing features and seizure classifiers, the features were hand-engineered, which may not be optimal. The main goal of the present paper is using deep convolutional neural networks (CNNs) and random forest to automatically optimize feature selection and classification. The input of the proposed classifier is raw multi-channel EEG and the output is the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(90 citation statements)
references
References 60 publications
0
90
0
Order By: Relevance
“…Recent research has also shown promising results for CNN-based EEG classification. In seizure detection (Acharya et al, 2018a;Ansari et al, 2018a), depression detection (Liu et al, 2017) and sleep stage classification (Acharya et al, 2018b;Ansari et al, 2018b), CNN have shown promising classification capabilities for EEG data. A CNN for EEG-based speech stimulus reconstruction was presented recently (de Taillez et al, 2017), showing that deep learning is a feasible alternative to linear decoding methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has also shown promising results for CNN-based EEG classification. In seizure detection (Acharya et al, 2018a;Ansari et al, 2018a), depression detection (Liu et al, 2017) and sleep stage classification (Acharya et al, 2018b;Ansari et al, 2018b), CNN have shown promising classification capabilities for EEG data. A CNN for EEG-based speech stimulus reconstruction was presented recently (de Taillez et al, 2017), showing that deep learning is a feasible alternative to linear decoding methods.…”
Section: Introductionmentioning
confidence: 99%
“…When we used a CNN, the best result was achieved with just two convolutional-pooling layers. In contrast, many researchers implemented more than 6 layers for the CNN 26,[37][38][39] . However, these studies did not include multiple fully connected hidden layers between the convolutional and output layers.…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies also show that heuristic algorithms can be developed to identify spike trains when the maximums of nonlinear energy components of the signal are compared to the background EEG activity, resulting in an overall good detection rate (GDR) of 95%, tested over 353 h recordings from 81 infants [35]. More recent work has demonstrated that a combinational scheme based on the convolutional neural networks (CNN) and random forest can help to automatically identify neonatal seizures in human babies with 77% overall accuracy [36].…”
Section: Related Workmentioning
confidence: 99%